The study of Airbnb application usage intention among Malaysians while travelling overseas - Ng, Yin Mei (2019)
The objective of this research is to study the usage intention of Airbnb mobile application among Malaysians while travelling overseas. It is essential to determine whether performance expectancy, effort expectancy, electronic word of mouth, trust and satisfaction affect usage intention of Airbnb mobile application among Malaysians when planning their travel itinerary. In this research, there were 382 of questionnaires have been collected from target respondents by using an online channel (Google Form). The data and results analysed by using Statistical Package Social Science (SPSS). The results of descriptive analysis of demographic profile, reliability test, Pearson Correlation Analysis and Multiple Linear Regression analysed. The results showed that performance expectancy is the most influential factor in the usage intention of Airbnb mobile application. Besides, the research finding shown effort expectancy and electronic word of mouth is insignificant to the usage intention of Airbnb mobile application. The limitation of this research is geographical location and time limitation. Due to insufficient time, the questionnaires were not distributed equally to all states in Malaysia, as well as unable to distribute evenly on demographic profile. For example, the percentage of undergraduate (education level) or students (employment status) were more than other groups. Therefore, it might lead to bias in data collection. Besides, as questionnaires distributed through online channel (Google Form) and without the assistance of researcher, respondents may not understand or misunderstand on some questions, and eventually mislead the respondents to answer wrongly. This study may help mobile service providers or marketers to understand more about users on using Airbnb application in developing markets, so that it will have better improvement on mobile app, while also providing a foundation and reference for future research studies, as well as for policymakers to have better understanding on mobile application and amend the policy accordingly, in order to protect all relevant parties.